Noise Induced Hearing Loss Iin Karachi An Lagnorant Prooblem - Iqbal hussain Udaipurwala (Journal of Bahria University Medical and Dental College)
Pakistan has a population of over 183 million and it is the world's sixth-most-populous country1.Karachi is the biggest and most populous metropolitan city of Pakistan with an estimated population of over 23.5 million people as reported in 2013. The approximate area of Karachi is 3,527 square km (1,362 square mile) resulting in a density of more than 6,000 people per square kilometer (15,500 per square mile)